Ultra‐Thick Paleoregolith Layer Detected by Lunar Penetrating Radar: Implication for Fast Regolith Formation Between 3.6 and 2.35 Ga - Tieyuan Zhu; Jinhai Zhang; Yangting Lin (Geophysical Research Letters)
Abstract Lunar paleoregolith was formed by repeated asteroid impact and space weathering and then buried by later lava flows, serving as important records for early solar system history. However, direct observational evidence for the paleoregolith layer is rather limited. We present the evidence for the existence of the paleoregolith layer by processing 60 MHz lunar penetrating radar data acquired by the Chang’E‐3 Yutu rover. We find successive reflections with reversed polarities due to a low permittivity (paleoregolith) layer sandwiched in two high permittivity (lava) layers. From modeling and migration imaging of radar reflections, we determine an ultra‐thick paleoregolith layer (∼5–9 m) beneath the Eratosthenian unit and on the top of the Imbrian unit, suggesting a high regolith production rate of 5.8–10.5 m/Ga between late Imbrian and early Eratosthenian periods compared to the previous estimation ∼2 m/Ga, implying fast regolith formation and possible high meteoric flux during these periods.